Calidad del sueño y rendimiento académico en los estudiantes de la Facultad de la Salud Humana de la Universidad Nacional de Loja - Silva Granda, María José (2021)
One of the relevant conditions for the optimal functioning of the organism is sleep. Its importance lies in the fact that it allows to restore and reorganize the cognitive functions involved in learning required during the day. Its value consists in its quality, that is, a sufficient number of hours of sleep. What is known about sleep is the reason to learn if the poor quality of it in students of the Faculty of Human Health of the National University of Loja is related to academic performance; this may be due to study schedules, night shifts, academic workload, emotional stress and level of demand, which affect their physical and mental health. Therefore, establishing the relationship between poor sleep quality and academic performance was sought. For this purpose, a quantitative, cross-sectional study was carried out in 307 randomly selected participants in whom sleep quality was assessed using the Pittsburg Index, and academic performance was obtained with the Grade Point Average of the last academic cycle. It was observed that 63.84% had poor sleep quality, more frequently in the female sex (45.9%). Very good academic performance corresponded to (19.54%) in whom there was no statistically significant relationship between the variables studied. Key words: sleep, academic performance, Pittsburg index.